For catching-by-polymerization oligo purification: scalable synthesis of the precursors to the polymerizable tagging phosphoramidites - Yin, Yipeng; Chillar, Komal; Apostle, Alexander; Halami, Bhaskar; Eriyagama, Adikari M. Dhananjani N.; Tanasova, Marina; Fang, Shiyue (PeerJ Organic Chemistry, 2024)
The catching-by-polymerization (CBP) oligodeoxynucleotide (oligo or ODN) purification method has been demonstrated suitable for large-scale, parallel, and long oligo purification. The authenticity of the oligos has been verified via DNA sequencing, and gene construction and expression. A remaining obstacle to the practical utility of the CBP method is affordable polymerizable tagging phosphoramidites (PTPs) that are needed for the method. In this article, we report scalable synthesis of the four nucleoside (dA, dC, dG and T) precursors to the PTPs using a route having five steps from inexpensive starting materials. The overall yields ranged from 21% to 35%. The scales of the synthesis presented here are up to 2.1 grams of the precursors. Because the syntheses are chromatography-free, further scaling up the syntheses of the precursors have become more feasible. With the precursors, the PTPs can be synthesized in one step using standard methods involving a chromatography purification.
Keywords: Catching-by-polymerization; Chromatography-free; Purification; Synthesis; Scalable; Tagging phosphoramidite; Long oligo